Investigation of the High Electron Affinity Molecular Dopant F6‐TCNNQ for Hole‐Transport Materials. (7th November 2017) - Zhang, Fengyu; Kahn, Antoine
Abstract: 2, 2′‐(perfluoronaphthalene‐2, 6‐diylidene)dimalononitrile (F6‐TCNNQ) is investigated as a molecular p‐type dopant in two hole‐transport materials, 2, 2′, 7, 7′‐tetrakis( N, N ‐diphenylamino)‐9, 9‐spirobifluorene (Spiro‐TAD) and tris(4‐carbazoyl‐9‐ylphenyl)amine (TCTA). The electron affinity of F6‐TCNNQ is determined to be 5.60 eV, one of the strongest organic molecular oxidizing agents used to date in organic electronics. p‐Doping is found to be effective in Spiro‐TAD (ionization energy = 5.46 eV) but not in TCTA (ionization energy = 5.85 eV). Optical absorption measurements demonstrate that charge transfer is the predominant doping mechanism in Spiro‐TAD:F6‐TCNNQ. The host–dopant interaction also leads to a significant alteration of the host film morphology. Finally, transport measurements done on Spiro‐TAD:F6‐TCNNQ as a function of dopant concentration and temperature, and using a highly doped contact layer to ensure negligible hole injection barrier, lead to an accurate measurement of the film conductivity and hole‐hopping activation energy. Abstract : 2, 2′‐(perfluoronaphthalene‐2, 6‐diylidene)dimalononitrile (F6‐TCNNQ) is investigated as p‐dopant in two hole‐transport materials (HTMs). Ultrathin, heavily doped 2, 2′, 7, 7′‐tetrakis( N, N ‐diphenylamino)‐9, 9‐spirobifluorene (Spiro‐TAD) injection layers are implemented to ensure a negligible hole injection barrier in transport measurements, allowing accurate determination of conductivity and carrier hopping activation energy in HTMs such as Spiro‐TAD.